2015
DOI: 10.1111/jth.12762
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and future risk of venous thromboembolism:the Tromsø study

Abstract: Summary. Aims: Whether atrial fibrillation is related to risk of venous thromboembolism (VTE) has not been extensively studied. Therefore, we investigated the association between atrial fibrillation and future risk of VTE in a population-based cohort. Methods: In total, 29 975 subjects were recruited from three surveys of the Tromsø study and followed from enrollment (1994-1995, 2001-2002 and 2007-2008) up to 2010. Incident events of atrial fibrillation and VTE during follow-up were recorded. Information on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 27 publications
9
62
1
6
Order By: Relevance
“…241 A Norwegian administrative database study reported that AF was associated with an increased risk of pulmonary embolism (adjusted HR, 1.83; 95% CI, 1.16–2.90) but not VTE (adjusted HR, 1.04; 95% CI, 0.64–1.68). 239 In addition, the same study found that individuals with incident VTE were subsequently at a higher risk of developing incident AF (adjusted HR, 1.63; 95% CI, 1.22–2.17) compared to those without VTE. 240 It should be noted that in both the Taiwanese and Norwegian cohorts, a significant proportion of individuals had pre-exiting RFs for VTE including lower extremity fracture, recent surgery, cancer, and immobility.…”
Section: Clinical Outcomesmentioning
confidence: 93%
See 2 more Smart Citations
“…241 A Norwegian administrative database study reported that AF was associated with an increased risk of pulmonary embolism (adjusted HR, 1.83; 95% CI, 1.16–2.90) but not VTE (adjusted HR, 1.04; 95% CI, 0.64–1.68). 239 In addition, the same study found that individuals with incident VTE were subsequently at a higher risk of developing incident AF (adjusted HR, 1.63; 95% CI, 1.22–2.17) compared to those without VTE. 240 It should be noted that in both the Taiwanese and Norwegian cohorts, a significant proportion of individuals had pre-exiting RFs for VTE including lower extremity fracture, recent surgery, cancer, and immobility.…”
Section: Clinical Outcomesmentioning
confidence: 93%
“…Potential direct causal relationship between AF and VTE has been proposed, but needs to be studied further. 239, 240 …”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…PEs can also originate from thrombi at the right side of the heart. Atrial fibrillation, pre‐disposing for intra‐cardiac thrombus formation, has been shown to be associated with VTE and PE in particular 14. Respiratory tract infection (RTI), including pneumonia, is associated with increased risk of VTE, and results from a case‐control study (the MEGA study) suggest that pneumonia has a stronger association with PE than DVT 6, 15.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence in high-income countries is 1–4%, but rises to more than 13% in individuals over 80 years of age. 2 Although embolic stroke is the most feared complication, over the past few decades AF has been associated with increased risk of myocardial infarction, 3 heart failure, 4 dementia, 5 chronic kidney disease, 6,7 venous thromboembolism, 8 and mortality. 9 Conversely, biologically plausible bidirectional relations have been reported, such that myocardial infarction, 10 heart failure, 10 chronic kidney disease, 6,7 and venous thromboembolism 11 are associated with increased risk of incident AF.…”
mentioning
confidence: 99%